Pengaruh Nanosilika terhadap Kekerasan dan Porositas Nanokomposit HA-SiO2 Berbasis Batuan Onyx Bojonegoro - Yudyanto Yudyanto; Yeyen Dwi Sugara; Hartatiek Hartatiek (Universitas Negeri Malang, 2016)
Hydroxyapatite (HA) is one of bioceramics which used in many biomedic applications. However, HA has poor mechanical properties. HA has be composited with material which has a good mechanical properties, such as nanosilica. In this study, synthesis HA was prepared by co-precipitation method. Base material to synthesis HA is onyx rock from Bojonegoro which contain 94.33 % Ca. While phosphate obtainable from Ammonium Dihydrogen Phosphate. The vickers hardness result using micro hardness vikers show that adding nanosilica is influence the mechanical properties of HA. The value of vikers hardness at adding nanosilica 10, 20, 30% respectively are 38.2; 42.3; 43.1 HVN while the porosity are 44.4; 40.7; 39.3 %. DOI: https://dx.doi.org/10.17977/um024v1i12016p013